2004
DOI: 10.1111/j.1559-1816.2004.tb02585.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Affirmative Action as a Function of the Strength of Ethnic Identity Among Latino College Students1

Abstract: The present study examined support for affirmative action among Latino college students as a function of ethnic identity. We found that, overall, Latino students generally endorsed affirmative action and did not feel undermined by it. Of primary interest to us was variation in support for affirmative action as a function of ethnic identity. The more the Latino students identified with their ethnic group, the more they endorsed affirmative action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 62 publications
(53 reference statements)
3
30
0
Order By: Relevance
“…Paralleling research on the relationship between ethnic identity salience and affirmative action (Snyder, Cleveland, & Thorton, 2006), Elizondo and Crosby (2004) found that Latino/a students who identified more strongly with their ethnic identity were more likely to support affirmative action. They also found that students who had advanced further in college were significantly more likely to support affirmative action, suggesting that progressing through college may influence a student's assessment of the policy.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Paralleling research on the relationship between ethnic identity salience and affirmative action (Snyder, Cleveland, & Thorton, 2006), Elizondo and Crosby (2004) found that Latino/a students who identified more strongly with their ethnic identity were more likely to support affirmative action. They also found that students who had advanced further in college were significantly more likely to support affirmative action, suggesting that progressing through college may influence a student's assessment of the policy.…”
Section: Introductionmentioning
confidence: 82%
“…Since the Supreme Court decision, citizens voted to ban affirmative action in Michigan and Nebraska, signaling that the debate over the policy will surely continue. A number of researchers have studied affirmative action attitudes within the college student population (Aberson, 2007;Elizondo & Crosby, 2004;Inkelas, 2003;Sax & Arredondo, 1999;Smith, 1998). However, few studies to date have looked at college student attitudes towards affirmative action over time.…”
Section: Introductionmentioning
confidence: 99%
“…Kluegel and Smith (1983) also reasoned that older White workers would be more likely to support AA because of their high tendency to have long tenure, seniority, and job security such that they would be less likely to be threatened by older Black workers. Due to the paucity of literature on the effects of age on support for AA, the analysis of age of research participants on support for AA in this study, will be an important contribution to knowledge, as well as fill an important age-related gap in literature, on workers' attitude toward AA.The pattern of findings in available research on the link between education and AA, showed that higher educational attainment is positively related to greater likelihood of support for AA (Elizondo & Crosby, 2004;Jacobson, 1983;Sidanius et al, 2008). Consistently with an earlier study by Jacobson (1983), Sidanius et al (2008) found that at the University of California, Los Angeles, White and Asian students increased their support for the university's race-ethnicbased AA programs, as these students advanced in education from first year to fourth year.…”
mentioning
confidence: 84%
“…People with higher levels of education generally tend to be more supportive of policies of AA than lesser educated people (Elizondo & Crosby, 2004;Sidanius et al, 2008). However, this interpretation may be challenged by the assumption asserted by Schaefer (1996), that educated people often gave socially desirable responses to survey questions dealing with racial matters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation